AGW 607- International Business Management (September 1997) - PPP, Pusat Pengajian Pengurusan (1997)
UNIVERSITI SAINS MALAYSIA Master of Business Administration First Semester Examination Academic Session 1997/98 September 1997 AGW 607- INTERNATIONAL BUSINESS MANAGEMENT Time : [3 hours] INSTRUCTIONS: Please make sure that this examination paper consists of TWO (2) printed pages before you begin. Answer questions ONE (1) and TWO (2) and THREE (3) other questions.